Bucky Fuller & Spaceship Earth - Foster, Norman, Fernández-Galiano, Luis (2010)
Breve reseña de la selección de contenidos de la revista.
Keywords: FULLER, R. BUCKMINSTER; ARQUITECTURA; CONSTRUCCION; ESTRUCTURAS; ESTADOS UNIDOS; HISTORIA; SIGLO XX